Herbicide Sprayer for the Tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The Overseas Division of the National Institute of Agricultural Engineering has come up with a herbicide sprayer that is cheap, safe and easy to use. This pull-along sprayer is small and light enough to be operated by one person. It is easy to use...